Risks, Management, and Prevention - Cunningham, Muriel (MD Conference Express, 2008)
The precise relative risk of stroke in pregnancy is not currently known, and the occurrence of stroke has dire consequences for both mother and fetus. According to the 2005 National Health Interview Survey, 253,000 women aged 18–44 years reported that they had been told by a clinician that they had suffered a stroke [Pleis et al. Vital Health Stat 2007]. This article discusses the risk of stroke and its relationship to ovarian hormones throughout the lifespan.